Inhibition effect of some benzylidenes on mild steel in 1M HCl: An experimental and theoretical correlation - Yadav D.K.; Quraishi M.A.; Maiti B. (My University, 2025)
The inhibition performance of four benzylidine malononitriles (BMNs) on mild steel (MS) in 1M HCl was studied by weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The associated activation energy (E a) and free energy of adsorption (ΔGads°) have been determined. The adsorption of inhibitors on MS surface obeyed the Langmuir's adsorption isotherm. Potentiodynamic polarization measurements showed that all inhibitors are mixed type. The energy dispersive X-ray (EDX) and scanning electron microscope (SEM) observations confirmed the existence of a protective film of inhibitor on MS surface. The results of the quantum chemical calculations were correlated with experimental inhibition efficiencies. © 2011 Elsevier Ltd.